Stop GnRH-Agonist Combined With Multiple-Dose GnRH-Antagonist Protocol for Patients With “Genuine” Poor Response Undergoing Controlled Ovarian Hyperstimulation for IVF - Raoul Orvieto; Raoul Orvieto; Michal Kirshenbaum; Valentina Galiano; Tal Elkan-Miller; Eran Zilberberg; Jigal Haas; Ravit Nahum (Frontiers in Endocrinology, 2020)
Objective: To examine whether the Stop GnRH-agonist combined with multiple-dose GnRH-antagonist protocol may improve conventional IVF/intracytoplasmic sperm injection (ICSI) cycle in poor ovarian response (POR) patients.Design: Cohort historical, proof of concept study.Setting: Tertiary, University affiliated Medical Center.Patient(s): Thirty POR patients, defined according to the Bologna criteria, who underwent a subsequent Stop GnRH-agonist combined with multiple-dose GnRH-antagonist controlled ovarian hyperstimulation (COH) protocol, within 3 months of the previous failed conventional IVF/ICSI cycle, were included. For the purposes of this study, we eliminated a bias in this selection by including only “genuine” poor responder patients, defined as those who yielded up to 3 oocytes following COH with a minimal gonadotropin daily dose of 300 IU.Main Outcome Measure(s): Number of oocytes retrieved, number of top-quality embryos, COH variables.Result(s): The Stop GnRH-agonist combined with multiple-dose GnRH-antagonist COH protocol revealed significantly higher numbers of follicles >13 mm on the day of hCG administration, higher numbers of oocytes retrieved, and top-quality embryos (TQE) with an acceptable clinical pregnancy rate (16.6%). Moreover, as expected, patients undergoing the Stop GnRH-agonist combined with multiple-dose GnRH-antagonist COH protocol required significantly higher doses and a longer duration of gonadotropins stimulation.Conclusion(s): The combined Stop GnRH-ag/GnRH-ant COH protocol is a valuable tool in the armamentarium for treating “genuine” poor ovarian responders. Further, large prospective studies are needed to elucidate its role in POR and to characterize the appropriate patients subgroup (before initiating ovarian stimulation) that may benefit from the combined Stop GnRH-ag/GnRH-ant COH protocol.